A Avaliação da Aprendizagem em Processo (AAP) a serviço da formação de formadores: limites e possibilidades - Sedemaca, Edislene (2017)
The main objective of this study is to investigate how teachers of Portuguese Language and Mathematics from a school in the city of Barueri state analyze and use the results presented in the Assessment of Learning in Process (AAP) to reassess their practices and to make decisions regarding the improvement of the quality of the students' education. The present research had a qualitative approach, characterized by data collected from semistructured interviews with four teachers who teach in High School, two of Portuguese Language and two of Mathematics and some observations in Classroom of Collective Pedagogical Work (ATPC) with The intention of knowing if there is room reserved at that moment for the discussion, the analysis and the interpretation of the results of the AAP. The specific objectives are to analyze if teachers are interested in making the AAP an instrument for replanning their practices, dedicating themselves to the student recovery process; To investigate how the results of AAP are interpreted by the teachers and what their reverberation in the actions practiced in the classroom. The AAP is an evaluation sent by the State Department of Education of São Paulo (SEE-SP), applied at the end of the three school years and aims to help teachers to diagnose the level of learning of students enrolled in the state school system. From the answers collected in the semi-structured interviews, seven categories of data analysis were attributed. In this way, we categorized the data collected, based on the interviewees' speeches and also on the main texts studied, that is, we separated units that served as classification criteria or facilitative codes to decode the data collected. Once this technique is adopted, we systematically try to verify the presence of structured elements in the categories by means of careful reading. After this procedure, we transcribed the answers of the interviewees and made the proper analysis. Once this work has been done, the data from the interviews will be presented and interpreted according to the following categories: 1. The role of the Pedagogical Coordinator, 2. Collaborative Work, 3. ATPC and School Planning as a training space, 4. The AAP as Formative evaluation, 5. The acting from the results, 6. The AAP as external or internal evaluation? 7. The Time to fulfill the Curriculum. For purposes of theoretical basis, we used several authors, among them: Hadji (2001), Bonamino (2002), Esteban (2003), Gatti (2003), Fiorentini (2006), Santos Guerra (2007), Luckesi (2011) e Alavarse et al. (2013)